2020
DOI: 10.34172/apb.2022.017
|View full text |Cite
|
Sign up to set email alerts
|

High Sensitivity Troponin T as Complementary Modality for Determining Doxorubicin Regimen Cardiotoxicity in Non-Hodgkin Lymphoma Patients

Abstract: Purpose: This study aims to evaluate the role of high-sensitivity troponin T (hsTnT) as a complementary tool for determining cardiotoxicity in non-Hodgkin lymphoma (NHL) patients receiving cyclophosphamide, doxorubicin, vincristine and prednisone (CHOP) regimen chemotherapy. Methods: We included 35 patients diagnosed with NHL who received CHOP chemotherapy. Left ventricular ejection fraction (LVEF) and hsTnT were measured at two time points: before the first cycle (pre-test) and after the fourth cycle (post-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 32 publications
(40 reference statements)
1
5
0
Order By: Relevance
“…However, when the detection time point was 3–6 months, the AUC increased to 0.90 (95% CI: 0.87–0.92), indicating a high early diagnostic value. This finding is consistent with results of previous studies 11,13,15,28 . Meta‐regression analysis showed that ethnicity and detection time point of hs‐cTnT were the main sources of heterogeneity, and sensitivity analysis showed that I 2 for sensitivity and specificity decreased to 30.46 (95% CI: 0.00–89.58) and 86.52 (95% CI: 77.86–95.17), respectively, after the exclusion of the study by Finke et al 20 .…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…However, when the detection time point was 3–6 months, the AUC increased to 0.90 (95% CI: 0.87–0.92), indicating a high early diagnostic value. This finding is consistent with results of previous studies 11,13,15,28 . Meta‐regression analysis showed that ethnicity and detection time point of hs‐cTnT were the main sources of heterogeneity, and sensitivity analysis showed that I 2 for sensitivity and specificity decreased to 30.46 (95% CI: 0.00–89.58) and 86.52 (95% CI: 77.86–95.17), respectively, after the exclusion of the study by Finke et al 20 .…”
Section: Discussionsupporting
confidence: 91%
“…This finding is consistent with results of previous studies. 11,13,15,28 Meta-regression analysis showed that ethnicity and detection time point of hs-cTnT were the main sources of heterogeneity, and sensitivity analysis showed that I 2 for sensitivity and specificity decreased to 30.46 (95% CI: 0.00-89.58) and 86.52 (95% CI: 77.86-95.17), respectively, after the exclusion of the study by Finke et al 20 This observation might result from different cut-off thresholds, study designs, patient populations, and treatments. Hs-cTnT had a PLR of 3.1 (95% CI: 1.8-5.4) and an NLR of 0.29 (95% CI: 0.17-0.50) for CTRCD diagnosis, suggesting that although the accuracy of diagnosing CTRCD patients was 3.1 times higher than that of judging healthy subjects, 29% of CTRCD patients might be missed.…”
Section: P P 2176mentioning
confidence: 99%
See 3 more Smart Citations